Dendritic morphology in the medial amygdala of adult male mice is unaffected by testosterone presence - Sharma, Loveena (Nanyang Technological University, 2021)
Steroid hormones have been implicated in brain-endocrine interaction, resulting in structural changes taking place in brain regions where receptors for these hormones can be found. This form of structural plasticity, where dendritic morphologies and arborization patterns are altered significantly, lead to changes in neuron firing patterns, which can cause downstream behavioural changes in the animal. While the neuroendocrinological changes conferred by several classes of steroid hormones, such as glucocorticoids, have been studied in detail, research on the effects of testosterone on structural plasticity have been relatively less studied. In this study, gonadectomized male mice are supplied with exogenous testosterone propionate or empty silastic tubing. Sections of their brains are stained with Golgi staining. Neuron populations from the following brain regions – the posterodorsal and posteroventral medial amygdala (MePD and MePV, respectively), medial pre-optic area (MPOA) and basolateral amygdala (BLA) – are isolated and examined in detail. Images of neurons in these regions are viewed from a bright field microscope, traced and processed according to a range of morphological parameters. Taking the midpoint of the soma as a reference, morphological characters such as the dendritic length, branch points and intersection points, are computed. Statistical analysis is done accordingly. Results indicate that there are no statistically significant changes in dendritic morphology among testosterone-supplemented mice and sham-supplemented mice in any of the brain regions examined in this study, suggesting that structural plasticity in the brain is not dependent on circulating testosterone levels, but on other factors present in the neuroendocrinological system.